(untitled) (Al-Mansour Journal, 2022)
Ternary Content Addressable Memories (TCAM) are the memories that search the data depend on the content stored in them. They are higher level than Content Addressable Memory (CAM) because they are search unknown value also i.e. ternary states, the ternary states is ternaryvalued logic or multi-valued logic, in CAM we refer to memory that is addressable by binary data while in TCAM means that the data may contain “don’t care” bits besides logic zero and logic one values. TCAM is used in network routers, ATM switch systems ,data compression. This paper presents FPGA design and simulation to test a TCAM cell for its search operation using VHDL language with ISE9.2i program and implemented on FPGA Altera DE2 kit.